2008
DOI: 10.1186/1750-1326-3-18
|View full text |Cite
|
Sign up to set email alerts
|

NG2 cells response to axonal alteration in the spinal cord white matter in mice with genetic disruption of neurofilament light subunit expression

Abstract: Background: Chondroitin sulphate proteoglycan (NG2) expressing cells, morphologically characterized by multi-branched processes and small cell bodies, are the 4 th commonest cell population of non-neuronal cell type in the central nervous system (CNS). They can interact with nodes of Ranvier, receive synaptic input, generate action potential and respond to some pathological stimuli, but the function of the cells is still unclear. We assumed the NG2 cells may play an active role in neuropathogenesis and aimed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Widespread axonal degeneration can lead to loss of oligodendrocytes and reactive changes in their progenitors 21, 22 , raising the possibility that degeneration of gray matter oligodendrocytes in ALS mice is secondary to motor neuron degeneration. To address whether loss of motor neurons is sufficient to induce mobilization of NG2 + cells, we partially ablated motor neurons by injecting ricin into the sciatic nerve 23 .…”
Section: Resultsmentioning
confidence: 99%
“…Widespread axonal degeneration can lead to loss of oligodendrocytes and reactive changes in their progenitors 21, 22 , raising the possibility that degeneration of gray matter oligodendrocytes in ALS mice is secondary to motor neuron degeneration. To address whether loss of motor neurons is sufficient to induce mobilization of NG2 + cells, we partially ablated motor neurons by injecting ricin into the sciatic nerve 23 .…”
Section: Resultsmentioning
confidence: 99%
“…NG2 has been demonstrated to be oligodendrocyte precursors (Kang et al, 2010; Nishiyama et al, 2009), and they promote oligodendrocytes proliferation during brain development and even in response to injury and demyelination (Girolamo et al, 2011; Kang et al, 2010). Indeed, NG2 has been considered an early sensor to deliver information about pathological changes in neurons to the local environment (Wu et al, 2008). Therefore, ethanol‐induced upregulation of NG2 might occur to compensate the myelin dysfunctions and neural damage observed in ethanol‐treated WT mice.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Monsma et al ( 2014 ) have shown that myelinating cells can regulate the rate of NF transport, resulting in local accumulation and expansion of the axonal diameter (Monsma et al, 2014 ), a process for which phosphorylation is most likely the mediator, given its upregulation during the process of myelination and studies such as Lee et al ( 2014 ), who demonstrated that MAPK cascades control anterograde transport of NFs. NF content does not determine the overall level of myelination: there are no significant differences in the expression of MAG between wildtype and NF knockouts (Wu et al, 2008 ). Although there appears to be no direct relationship between the level of myelination of an axon and its NF content, the level of myelination may nonetheless affect the level of axonal NF phosphorylation.…”
Section: Posttranslational Modifications Of Neurofilamentsmentioning
confidence: 99%